(untitled) (International relations and international law Journal, 2019)
In modern society legal support of activity of agricultural cooperatives is one of the crucial direction of jurisprudence. This trend is seen not only in the practice of Kazakhstan, but nevertheless also abroad. Modern civilization is forced to develop agricultural cooperatives, due to the urgent need to ensure food security. Therefore, associations in cooperatives can significantly improve agricultural income, which will positively affect the development of the economy as a whole. The purpose of this article is to study the legislation of foreign countries in the field of agricultural cooperatives. Make a comparative legal analysis of the legal framework of some foreign countries in the field. To create scientific conclusions and proposals for improving public policy in this area. The results of this study can be used in the scientific materials of subsequent studies. The study of this topic is necessary for several reasons. First, the study identified some gaps in domestic legislation in this area and proposed specific solutions to these problems. Secondly, the authors proposed specific recommendations for improving the agricultural legislation of our Republic. The authors also identified the importance and role of agricultural cooperatives and possible directions of its development. In the final part, the authors note that for the objective and comprehensive development of agricultural cooperatives, first of all, it is necessary to have quality legislation. That is, without proper regulation it is impossible to get proper development. And also in the first the concept of economic instruments of development of agricultural cooperatives is used. Key words: agricultural cooperation, agrarian legislation, pratique of foreign States, economic mechanism, state policy.